NADPH oxidase 4 deficiency attenuates experimental osteoarthritis in mice. Issue 1 (21st February 2023) - Renaudin, Félix; Oudina, Karim; Gerbaix, Maude; McGilligan Subilia, Manon; Paccaud, Joris; Jaquet, Vincent; Krause, Karl-Heinz; Ferrari, Serge; Laumonier, Thomas; Hannouche, Didier
Abstract : Objective: Low-grade inflammation plays a pivotal role in osteoarthritis (OA) through exposure to reactive oxygen species (ROS). In chondrocytes, NADPH oxidase 4 (NOX4) is one of the major ROS producers. In this study, we evaluated the role of NOX4 on joint homoeostasis after destabilisation of the medial meniscus (DMM) in mice. Methods: Experimental OA was simulated on cartilage explants using interleukin-1β (IL-1β) and induced by DMM in wild-type (WT) and NOX4 knockout (NOX4 -/- ) mice. We evaluated NOX4 expression, inflammation, cartilage metabolism and oxidative stress by immunohistochemistry. Bone phenotype was also determined by micro-CT and histomorphometry. Results: Whole body NOX4 deletion attenuated experimental OA in mice, with a significant reduction of the OARSI score at 8 weeks. DMM increased total subchondral bone plate (SB.Th), epiphysial trabecular thicknesses (Tb.Th) and bone volume fraction (BV/TV) in both NOX4 -/- and wild-type (WT) mice. Interestingly, DDM decreased total connectivity density (Conn.Dens) and increased medial BV/TV and Tb.Th only in WT mice. Ex vivo, NOX4 deficiency increased aggrecan (AGG) expression and decreased matrix metalloproteinase 13 (MMP13) and collagen type I (COL1) expression. IL-1β increased NOX4 and 8-hydroxy-2'-deoxyguanosine (8-OHdG) expression in WT cartilage explants but not in NOX4 -/- . In vivo, absence of NOX4 increased anabolism and decreased catabolism after DMM. Finally, NOX4 deletion decreased synovitis score, 8-OHdG and F4/80 staining following DMM. Conclusion: NOX4 deficiency restores cartilage homoeostasis, inhibits oxidative stress, inflammation and delays OA progression after DMM in mice. These findings suggest that NOX4 represent a potential target to counteract for OA treatment.